Influence of substrate annealing on inducing Ti3+ and oxygen vacancy in TiO2 thin films deposited via RF magnetron sputtering - Abdullah, S.A.; Sahdan, M.Z.; Nafarizal, N.; Saim, H.; Embong, Z.; Cik Rohaida, C.H.; Adriyanto, F. (ScienceDirect, 2018)
Nano-crystalline TiO2 has been prepared by RF magnetron sputtering at varied substrate temperatures ranging from 200 to 500 °C. The alteration of oxygen and titanium atom in TiO2 at uppermost surface is clearly observed on the effect of annealing temperature by Auger Electron Spectroscopy (AES) technique. The measurement of peak to peak value of Ti and O transition line at 400 °C indicates the surface chemical state of O2 in TiO2 thin films defect at surface and Fermi level was analyzed using the X-Ray Photoelectron Spectroscopy (XPS). The Ti 2p observation of pre and post surface treatment shows the concentration of Ti3+ is seven times higher after post sputtered for sample 200 °C. Ti3+ decrease by increasing temperature. The Ti3+-oxygen vacancy which also assigned as Ti2O3 occurred in all sample, yet sample deposited at 400 °C gives nearest binding energy for Ti2O3. This observation also supported by The Time of Flight Secondary Ion Mass Spectrometry (ToF-SIMS) analysis which shows highest total ion count for positive polarity is O+ for sample at 300 °C and Ti ion dominant is Ti2O3 + for sample at 400 °C. Based on the analyses, it is clearly seen that high defect of Ti3+-oxygen vacancy which is located between surface layer and fermi level state, this defect levels was created at surface layer at low annealing temperature. However, increasing temperature leads to defect creation on bellow surface layer which consider as within fermi level layer